Who Wants to be a Millionaire? : The Bumper Quiz Book - Boxtree (London Boxtree, 2000)
Based on the hugely successful "Who Wants to Be A Millionaire" television show. The 2000 questions in this book are written by the programme's question masters. So what better way to find out if you really could be a million pounds better off
Keywords: Questions and answers -- Television quiz shows -- Radio quiz shows